Student career preparation strategies through workforce agility: A systematic literature review and bibliometric analysis - Anggeraini, Lia; Hidayati, Ira; Wahyuni, Citra (Universitas Islam Negeri Raden Intan Lampung, 2024)
In this era, employees are required to have the ability to respond and adapt quickly to change, known as workforce agility. This study aims to explain the dimensions and factors that can affect workforce agility. The research was conducted by systematic literature review (SLR), using PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) and Bibliometric methods to filter topics, subtopics, and journals that fit the criteria. 42 journals were obtained from the database, namely Sciencedirect, Emerald, PubMed, Google Scholar, Semantic Scholar, and Mendeley Web Importer. Based on the results of research that has been done, workforce agility is influenced by Psychological Empowerment (18%), Leadership (14%), Organizational Culture (10%), Workplace Spirituality (10%), Enterprise Social Media (ESM) (9%), Knowledge Management (8%), Organizational Learning (7%), Innovative Work Behavior (7%), Emotional Intelligence (3%), and Job Satisfaction (2%). Employees who have high agility are usually adaptable to changing situations, tasks, and new technologies, and are able to work in a variety of dynamic conditions.